Proteomic analysis of integrin‐associated complexes from mesenchymal stem cells. Issue 1 (17th September 2015) - Ajeian, Jila N.; Horton, Edward R.; Astudillo, Pablo; Byron, Adam; Askari, Janet A.; Millon‐Frémillon, Angélique; Knight, David; Kimber, Susan J.; Humphries, Martin J.; Humphries, Jonathan D.
Abstract : Purpose: Multipotent mesenchymal stem cells (MSCs) have the capability to differentiate down adipocyte, osteocyte and chondrocyte lineages and as such offer a range of potential therapeutic applications. The composition and stiffness of the extracellular matrix (ECM) environment that surrounds cells dictates their transcriptional programme, thereby affecting stem cell lineage decision‐making. Cells sense force via linkages between themselves and their microenvironment, and this is transmitted by integrin receptors and associated adhesion signalling complexes. To identify regulators of MSC force sensing, we sought to catalogue MSC integrin‐associated adhesion complex composition. Experimental design: Adhesion complexes formed by MSCs plated on the ECM ligand fibronectin were isolated and characterised by MS. Identified proteins were interrogated by comparison to a literature‐based reference set of cell adhesion‐related components and using ontological and protein–protein interaction network analyses. Results: Adhesion complex‐specific proteins in MSCs were identified that comprised predominantly cell adhesion‐related adaptors and actin cytoskeleton regulators. Furthermore, LIM domain‐containing proteins in MSC adhesion complexes were highlighted, which may act as force‐sensing components. Conclusion and clinical relevance: These data provide a valuable resource of information regarding the molecular connections that link integrins and adhesion signalling in MSCs, and as such may present novel opportunities for therapeutic intervention.